Relationship Between Age, Gender, and Race in Patients Presenting With Myasthenia Gravis With Only Ocular Manifestations. Issue 1 (March 2016) - Peragallo, Jason H.; Bitrian, Elena; Kupersmith, Mark J.; Zimprich, Fritz; Whittaker, Thomas J.; Lee, Michael S.; Bruce, Beau B.
Abstract : Background: The demographic associations among patients presenting with myasthenia gravis with only ocular manifestations (OMG) is not clear. Methods: In this 5-center case series, we collected the race, gender, and age at diagnosis of patients diagnosed with myasthenia gravis who had no signs or symptoms of generalized myasthenia gravis (GMG). An a priori sample size calculation determined that 140 patients were required to accept that there was a ⩽10-year difference in mean age (equivalence testing: power 90%, α = 0.05). Robust Bayesian analysis and linear regression were applied to evaluate whether age differed by gender or race. Results: Of 433 patients included, 258 (60%) were men. Mean age among men was 57 years (SD = 19) and 52 years (SD = 21) among women. The 95% credible interval (CI) (Bayesian equivalent of confidence interval) was 0.8–8.7 years for mean age, and there was a 99.6% probability that the mean difference in age between sexes was <10 years. Race was documented in 376 (68 [18%] non-Caucasian). Caucasians were 17.3 years older than non-Caucasians at diagnosis (95% CI, 12.2–22.3 y; P < 0.001) controlling for gender. There was no additive interaction of gender and race ( P = 0.74). There was a bimodal distribution for women peaking around 30 and 60 years. Men had a left skewed unimodal age distribution peaking at age 70. Conclusions: The distribution of age at presentation in patients with OMG is different between men and women, similar to GMG. Non-Caucasian patients tend to develop OMG at a younger age.